Alphabetic Knowledge and Phonological Awareness : A comparison between Malaysian Preschool Children from Public and Private Kindergartens - Julia Ai Cheng, Lee; Wang,, Joanna Joo Ying (UNIMAS Publisher, 2020)
Alphabetic knowledge and phonological awareness are essential skills in learning to read. This research examined the level of acquisition on alphabetic knowledge and phonological awareness among 60 preschoolers from private and public preschools in Kuching, Sarawak. The mean age of the children was 5.58. The children were administered letter name and sound knowledge, and letter naming fluency tests to examine their alphabetic knowledge; Comprehensive Test of Phonological Processing and Yopp-Singer Phoneme Segmentation Test to examine their phonological awareness. Higher achievement in alphabetic knowledge and phonological awareness was found among preschoolers from private preschools compared to those from public preschools. This study discusses the implications for practice and the ways teachers could explicitly foster alphabetic knowledge and phonological awareness skills in the classroom.